2021
DOI: 10.22435/blb.v17i1.2612
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira pada Tikus dan Badan Air serta Riwayat Penularan Penderita di Daerah Baru Kasus Leptospirosis di Bantul

Abstract: In 2017 leptospirosis cases occur in new areas in Bantul where cases have never been previously reported. Cases still occur in 2018 with an interval of two months after the first case. Preventive and curative efforts in the context of controlling cases have been carried out by the local health office, in addition to these control efforts, it is also necessary to know the presence of Leptospira in rats and water bodies in the area as well as the history of patients transmission. This study was conducted to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Research conducted by Izquierdo-Rodríguez et al ( 2020) and Udechukwu et al (2021) has consistently demonstrated a higher prevalence of leptospirosis in Rattus norvegicus compared to other rat species (Izquierdo-Rodríguez et al, 2020;Udechukwu et al, 2021). One contributing factor to this elevated prevalence of pathogenic Leptospira infection in Rattus norvegicus is their habitat, often characterized by high humidity and moisture levels, which create an environment conducive to the survival and proliferation of Leptospira bacteria (Sholichah, Wahyudi, et al, 2021).…”
Section: Resultsmentioning
confidence: 97%
“…Research conducted by Izquierdo-Rodríguez et al ( 2020) and Udechukwu et al (2021) has consistently demonstrated a higher prevalence of leptospirosis in Rattus norvegicus compared to other rat species (Izquierdo-Rodríguez et al, 2020;Udechukwu et al, 2021). One contributing factor to this elevated prevalence of pathogenic Leptospira infection in Rattus norvegicus is their habitat, often characterized by high humidity and moisture levels, which create an environment conducive to the survival and proliferation of Leptospira bacteria (Sholichah, Wahyudi, et al, 2021).…”
Section: Resultsmentioning
confidence: 97%
“…Leptospira yang ditularkan oleh hewan pembawa bakteri terutama tikus. Penderita leptospirosis di Indonesia pada 12 provinsi selama tahun 2005-2019, sedangkan hewan yang terdeteksi sebagai pembawa Leptospira telah ditemukan di 25 provinsi (Sholichah et al, 2021).…”
Section: Penyakit Ini Disebabkan Oleh Bakteriunclassified